Učinkovitost raztopin elektrolitov in raztopin koloidov z elektroliti pri preprečevanju hipotenzije po subarahnoidni anesteziji - Kamenik, Mirt (Medicinski razgledi, 2001)
Hypotension following spinal anesthesia, a well-known of this anesthetic technique, is caused by the blockade of the sympathetic nervous system. An infusion of crystalloid or colloid solutions before the block is one possibility for decreasing the incidence of hypotension following spinal anesthesia. The article is a review of literature about the effectiveness of the infusion of crystalloid or colloid solutions before spinal anesthesia in the prevention of hypotension after spinal anesthesia. An infusion of a crystalloid solution before spinal anesthesia causes a small, statistically insignificant decrease in the incidence of hypotension after spinal anesthesia, which is not clinically important. Most studies report a statistically significant decrease in the incidence of hypotension after spinal anesthesia with an infusion of colloid solution before spinal anesthesia. However, it is impossible to completely prevent hypotension after spinal anesthesia even with an infusion of a colloid before administering blockade.
Keywords: Anestezija, spinalna; Anesthesia, spinal; Adverse effects; Škodljivi učinki; Subarachnoid space; Subarahnoidni prostor; Hipotenzija; Hypotension; Electrolytes; Elektroliti; Koloidi; Colloids; anestezija; spinalna anestezija